Method for recycling positive electrode sheet waste, positive electrode sheet and lithium ion battery

CN122931124APending Publication Date: 2026-10-16MIRATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611195372.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

传统借鉴退役电池的固定参数烧结工艺,仅能适配状态相对均一的正极极片废料,同时也难以抵消不同批次正极极片废料在粘结剂用量和碳含量等差异,固定的烧结温度与保温时长参数易引发欠烧或过烧问题,难以保障不同批次间正极极片废料回收到的磷酸铁锂产品性能的一致性

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931124A_ABST
    Figure CN122931124A_ABST
Patent Text Reader

Abstract

The application provides a positive electrode sheet waste recycling method, a positive electrode sheet and a lithium ion battery, and comprises the following steps: stripping a positive electrode active material layer from the positive electrode sheet waste, sequentially performing vacuum drying treatment and calcination treatment on the positive electrode active material to obtain lithium iron phosphate; the mass content of water in the positive electrode active material after the vacuum drying treatment is controlled to be less than or equal to 4000 ppm; the cumulative loss on ignition of the positive electrode active material is monitored in the calcination treatment, and when the cumulative loss on ignition is 1.7wt%-1.8wt%, the heating is stopped and the cooling treatment is performed. The positive electrode active material stripped from the positive electrode sheet waste is sequentially subjected to vacuum drying treatment and calcination treatment according to the recycling method; the cumulative loss on ignition can reflect the progress of the decomposition of the binder and the generation of amorphous carbon, and a specific cumulative loss on ignition can guarantee the consistency of the repair degree of lithium iron phosphate in the positive electrode sheet waste, avoid over-burning or under-burning, and recycle the lithium iron phosphate with stable quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery recycling technology, and in particular to a method for recycling waste positive electrode sheets, positive electrode sheets, and lithium-ion batteries. Background Technology

[0002] In the manufacturing process of lithium batteries, positive electrode waste is inevitably generated. This waste contains positive electrode active materials with a complete crystal structure, free from SEI film formation, electrolyte residue, and severe lattice lithium deficiency defects, possessing superior original structure and utilization value. Traditional fixed-parameter sintering processes, borrowed from retired batteries, are only suitable for relatively uniform positive electrode waste. Furthermore, they struggle to compensate for differences in binder dosage and carbon content between different batches of waste positive electrode material. Fixed sintering temperature and holding time parameters easily lead to under-sintering or over-sintering problems, making it difficult to guarantee the consistency of performance of lithium iron phosphate products recovered from different batches of waste positive electrode material. Summary of the Invention

[0003] Therefore, it is necessary to provide a method for recycling waste positive electrode sheets, positive electrode sheets, and lithium-ion batteries, aiming to ensure the consistency of the quality of the recycled lithium iron phosphate.

[0004] One aspect of the present invention provides a method for recycling waste positive electrode sheets, comprising the following steps:

[0005] The positive electrode active material layer is peeled off from the positive electrode waste, and the positive electrode active material is subjected to vacuum drying and calcination treatment in sequence to obtain lithium iron phosphate.

[0006] The water content in the positive electrode active material after vacuum drying is controlled to be ≤4000ppm; the cumulative burn-off rate of the positive electrode active material is monitored during the calcination process, and when the cumulative burn-off rate is 1.7wt%~1.8wt%, calcination is stopped and cooling treatment is initiated.

[0007] The above-mentioned method for recycling positive electrode waste involves sequentially vacuum drying and calcining the positive electrode active material stripped from the waste. Vacuum drying controls the moisture content of the positive electrode active material to a low level, unifying its initial state. Calcination promotes the pyrolysis of the binder and the conversion of binder pyrolysis products and / or conductive carbon into an amorphous carbon network. The cumulative loss on ignition reflects the degree of binder decomposition and the progress of amorphous carbon formation. A cumulative loss on ignition within a specific water range ensures the consistency of the repair degree of lithium iron phosphate in the positive electrode waste, avoiding over-burning or under-burning, achieving intelligent and adaptive production, and recovering stable quality lithium iron phosphate.

[0008] Furthermore, if the moisture content is too high, it will interfere with the reaction process during calcination. Therefore, the cumulative loss on ignition cannot accurately reflect the progress of the reaction. Controlling the moisture content at a low level can improve the representativeness of the cumulative loss on ignition for the reaction during calcination. This makes the direct regeneration process, which uses closed-loop monitoring of the cumulative loss on ignition to control the calcination endpoint, more universal and accurate.

[0009] In particular, the above-mentioned method for recycling positive electrode waste can be used to simultaneously recycle the same or different batches of positive electrode waste. Through the control of the above recycling process, the initial state of the positive electrode active material can be better unified, the consistency of the repair degree of lithium iron phosphate in the positive electrode waste can be improved, and stable quality lithium iron phosphate can be obtained.

[0010] In some embodiments, the calcination treatment satisfies one or more of the following conditions:

[0011] (1) The calcination process is set to a temperature of 450℃~500℃;

[0012] (2) The calcination process is set to last for 1 to 2 hours;

[0013] (3) The heating rate of the calcination treatment is 3℃ / min to 7℃ / min;

[0014] (4) The calcination process is carried out in an inert gas with a flow rate of 0.5 L / min to 5 L / min.

[0015] In some embodiments, the vacuum drying process satisfies one or more of the following conditions:

[0016] (1) The vacuum degree of the vacuum drying process is -0.05MPa to -0.1MPa;

[0017] (2) The drying temperature of the vacuum drying process is 100℃~150℃;

[0018] (3) The drying time of the vacuum drying process is 30 min to 150 min.

[0019] In some embodiments, after the positive electrode active material undergoes the vacuum drying process and before the calcination process, the following steps are also included:

[0020] The positive electrode active material, after being vacuum dried, is coarsely crushed to D90 < 100 μm to obtain coarsely crushed positive electrode active material.

[0021] In some embodiments, different batches of the coarsely crushed positive electrode active material are mixed, and the mixing process satisfies one or more of the following conditions:

[0022] (1) The rotation speed of the mixing process is 25 rpm to 40 rpm;

[0023] (2) The mixing time is 15 min to 120 min;

[0024] (3) The temperature of the mixing process is 25℃~50℃;

[0025] (4) The atmosphere of the mixed treatment is one or more of air atmosphere and nitrogen atmosphere.

[0026] In some embodiments, after the calcination treatment and before obtaining the lithium iron phosphate, the following steps are further included:

[0027] The lithium iron phosphate obtained from the calcination treatment is subjected to fine crushing treatment to control the D50 of the obtained lithium iron phosphate to be 1μm~5μm.

[0028] In some embodiments, the positive electrode active material layer is peeled off from the positive electrode waste, including the following steps:

[0029] The positive electrode waste is soaked in water and separated to obtain the positive electrode active material.

[0030] In another aspect, the present invention provides a lithium iron phosphate, which is recovered using the above-described method for recycling positive electrode waste.

[0031] In another aspect, the present invention provides a positive electrode sheet comprising the aforementioned lithium iron phosphate.

[0032] In another aspect, the present invention provides a lithium-ion battery comprising the above-described positive electrode, negative electrode, and a separator and / or electrolyte disposed between the positive electrode and the negative electrode. Attached Figure Description

[0033] Figure 1 A schematic flowchart illustrating a method for recycling waste positive electrode sheets according to one embodiment;

[0034] Figure 2 The graph shows a comparison of the electrochemical performance of lithium iron phosphate in Examples 1-3 and Comparative Examples 1-2.

[0035] Figure 3 The graph shows a comparison of the cycle performance of lithium iron phosphate in Examples 1, 4 to 7. Detailed Implementation

[0036] To facilitate understanding of the present invention, a more complete description will be given below with reference to relevant embodiments. Preferred embodiments of the invention are shown below. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that a thorough and complete understanding of the disclosure of the invention will be achieved.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0038] Please see Figure 1 One embodiment of this application provides a method for recycling waste positive electrode sheets, including the following step S10:

[0039] S10. The positive electrode active material layer is peeled off from the positive electrode waste, and the positive electrode active material is subjected to vacuum drying and calcination treatment in sequence to obtain lithium iron phosphate.

[0040] In S10, the water content in the waste lithium iron phosphate after vacuum drying and before calcination is controlled to be ≤4000ppm; during calcination, the cumulative burn-off rate of the waste lithium iron phosphate is monitored, and when the cumulative burn-off rate is 1.7wt%~1.8wt%, heating is stopped and cooling is initiated.

[0041] The above-mentioned method for preparing recycled lithium iron phosphate involves sequentially subjecting the positive electrode active material stripped from the waste positive electrode sheet to vacuum drying and calcination. Vacuum drying controls the moisture content of the positive electrode active material to a low level, unifying its initial state. Calcination promotes the pyrolysis of the binder and the conversion of binder pyrolysis products and / or conductive carbon into an amorphous carbon network. The cumulative burn-off rate reflects the degree of binder decomposition and the progress of amorphous carbon formation. A cumulative burn-off rate within a specific water range ensures the consistency of the lithium iron phosphate repair in the waste positive electrode sheet, avoiding over-burning or under-burning, achieving intelligent and adaptive production, and recovering lithium iron phosphate with stable quality.

[0042] Furthermore, if the moisture content is too high, it will interfere with the reaction process during calcination. Therefore, the cumulative loss on ignition cannot accurately reflect the progress of the reaction. Controlling the moisture content at a low level can improve the representativeness of the cumulative loss on ignition for the reaction during calcination. This makes the direct regeneration process, which uses closed-loop monitoring of the cumulative loss on ignition to control the calcination endpoint, more universal and accurate.

[0043] In particular, the above-mentioned method for recycling positive electrode waste can be used to simultaneously recycle the same or different batches of positive electrode waste. Through the control of the above recycling process, the initial state of the positive electrode active material can be better unified, the consistency of the repair degree of lithium iron phosphate in the positive electrode waste can be improved, and stable quality lithium iron phosphate can be obtained.

[0044] In some embodiments, the positive electrode waste comes from positive electrode scraps and / or waste materials generated in the lithium battery production process, as well as secondary positive electrode sheets generated due to process upgrades and / or changes in acceptance standards, i.e., positive electrode waste that has not participated in the charge and discharge reaction and has not been injected with liquid.

[0045] Understandably, the binder content, conductive agent content, and coating thickness of positive electrode waste from the same or different batches are not entirely the same.

[0046] Understandably, the cumulative burn-off rate is the percentage of the difference between the initial mass of the positive electrode active material at the start of the calcination process and the mass measured in real time at a certain point in the calcination process, and the initial mass at the start of the calcination process. Cumulative burn-off rate = (M0 - M...) t ) / M0×100%, where M0 represents the initial mass at the start of the calcination treatment, M t This indicates the mass measured in real time at a certain point during the calcination process.

[0047] Understandably, the cumulative burn-off rate is measured in real time by an online thermogravimetric monitoring system. Sensors record the mass signal of the positive electrode active material during the calcination process and transmit the mass change signal to the control system in real time to calculate the cumulative burn-off rate. When the cumulative burn-off rate reaches 1.7wt%~1.8wt%, heating is stopped and cooling begins. This means that the actual calcination time and / or actual temperature are controlled by the cumulative burn-off rate of 1.7wt%~1.8wt%. As soon as the cumulative burn-off rate enters the 1.7wt%~1.8wt% window, heating for calcination is stopped and cooling begins to obtain the product. This implies that even if the set temperature and / or set time for calcination are not reached, the process must stop once the cumulative burn-off rate is reached, and no further calcination is performed after stopping; instead, cooling begins to obtain the product.

[0048] In some embodiments, the water content in the positive electrode active material after vacuum drying and before calcination is 500 ppm to 4000 ppm by mass. As an example, the water content of the positive electrode active material may be 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, or any two of the above values.

[0049] In some embodiments, the calcination process is programmed to a temperature of 450°C to 500°C. As an example, the calcination process may be programmed to a temperature of 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, or any two of the above values.

[0050] In some embodiments, the calcination process is set to a duration of 1 to 2 hours. As an example, the calcination process duration can be 1 hour, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2 hours, or any two of the above values.

[0051] In some embodiments, the heating rate of the calcination treatment is 3°C / min to 7°C / min. As an example, the heating rate of the calcination treatment may be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, or any two of the above values, for example, 4°C / min to 6°C / min.

[0052] In some embodiments, the calcination process is carried out in an inert gas with a flow rate of 0.5 L / min to 5 L / min. As an example, the inert gas flow rate may be 0.5 L / min, 1 L / min, 1.5 L / min, 2 L / min, 2.5 L / min, 3 L / min, 3.5 L / min, 4 L / min, 4.5 L / min, 5 L / min, or any two of the above values.

[0053] In some embodiments, after vacuum drying the positive electrode active material and before calcination, the following steps are also included:

[0054] The positive electrode active material after vacuum drying is coarsely crushed to D90 < 100 μm to obtain coarsely crushed positive electrode active material.

[0055] Understandably, D90 represents the particle size at which the cumulative volume distribution in the system reaches 90%, that is, particles smaller than 100μm account for 90% of the total volume in the coarse crushed material.

[0056] In some embodiments, coarse crushing is performed by one or more of a jaw crusher, gyratory crusher, hammer crusher, and air jet crusher.

[0057] In some embodiments, the coarsely crushed positive electrode active material is mixed using one or more of a V-type mixer, a vertical mixer, a horizontal mixer, a plow mixer, a paddle mixer, and a continuous mixer.

[0058] In some embodiments, the mixing speed is 25 rpm to 40 rpm.

[0059] In some embodiments, the mixing time is 15 min to 120 min.

[0060] In some embodiments, the mixing temperature is 25°C to 50°C.

[0061] In some embodiments, the atmosphere for the mixed processing is one or more of an air atmosphere and a nitrogen atmosphere.

[0062] In some embodiments, the following steps are included after calcination and before obtaining lithium iron phosphate:

[0063] The lithium iron phosphate obtained by calcination was subjected to fine crushing to control the D50 of the obtained lithium iron phosphate to be 1μm~5μm.

[0064] Understandably, D50 represents the particle size at which the cumulative volume distribution in the system reaches 50%, that is, particles with a diameter of 1μm to 5μm account for 50% of the total volume in lithium iron phosphate after fine crushing.

[0065] In some embodiments, fine crushing is performed using one or more of a cone crusher, impact crusher, counter-impact crusher, air jet mill, and double roll crusher.

[0066] In some embodiments, the positive electrode active material layer is peeled off from the positive electrode waste, including the following steps:

[0067] The positive electrode waste is soaked in water and separated to obtain the positive electrode active material.

[0068] Another embodiment of this application provides a lithium iron phosphate, which is recovered using the above-described method for recycling positive electrode waste.

[0069] Another embodiment of this application provides a positive electrode sheet comprising the aforementioned lithium iron phosphate.

[0070] In some embodiments, the positive electrode sheet includes an aluminum foil current collector and a positive electrode film layer disposed on at least one side of the aluminum foil current collector. The positive electrode film layer includes the aforementioned lithium iron phosphate, positive electrode conductive agent, and positive electrode binder.

[0071] In some embodiments, the aluminum foil current collector includes an aluminum foil and a carbon coating layer disposed on at least one side of the aluminum foil, the carbon coating layer including a carbon material and a binder.

[0072] In some embodiments, the positive conductive agent includes one or more of graphite, graphene, conductive carbon black, acetylene black, carbon nanotubes, and carbon fibers.

[0073] In some embodiments, the positive electrode binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyimide, polyaniline, sodium carboxymethyl cellulose, lithium-ionized polyacrylic acid, guar gum, and sodium alginate.

[0074] Another embodiment of this application provides a lithium-ion battery, including the above-mentioned positive electrode, negative electrode, and a separator and / or electrolyte disposed between the positive electrode and the negative electrode.

[0075] In some embodiments, the negative electrode sheet includes a copper foil current collector and a negative electrode film layer disposed on at least one side of the copper foil current collector. The negative electrode film layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.

[0076] In some embodiments, the negative electrode active material includes one or more of lithium metal, graphite, amorphous carbon, and silicon-based materials.

[0077] In some embodiments, the negative electrode conductive agent includes one or more of graphite, graphene, conductive carbon black, acetylene black, carbon nanotubes, and carbon fibers.

[0078] In some embodiments, the negative electrode binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber.

[0079] In some embodiments, the diaphragm includes one or more of a polyethylene diaphragm, a polypropylene diaphragm, and a composite diaphragm. The composite diaphragm includes a polypropylene membrane, a polyethylene membrane, and a polypropylene membrane arranged in sequence.

[0080] In some embodiments, the electrolyte includes one or more of liquid electrolytes, solid electrolytes, and gel electrolytes.

[0081] The following are specific examples.

[0082] Example 1

[0083] Please see Figure 1 The preparation method of recycled lithium iron phosphate includes the following steps:

[0084] S1. Soaking and detachment. The unfilled positive electrode waste is soaked in water at 40℃±10℃ and stirred continuously for 30min±5min. The aluminum foil is removed by filtration, and then allowed to stand for solid-liquid separation to obtain the positive electrode active material.

[0085] S2. Vacuum drying. The positive electrode active material from step S1 is placed in a vacuum drying oven for 120 min ± 10 min. The vacuum degree inside the drying oven is -0.09 MPa ± -0.01 MPa, and the temperature is 135℃ ± 15℃. The water content of the positive electrode active material after vacuum drying is 1500 ppm.

[0086] S3. Coarse crushing. The positive electrode active material that has been vacuum dried in step S2 is subjected to airflow crushing until D90 < 100 μm.

[0087] S4. Mixing. The coarsely crushed positive electrode active material from step S3 is added to a V-type mixer and mixed for 30 min ± 5 min at a mixer speed of 30 rpm ± 5 rpm. The coefficient of variation (CV) of the mixed positive electrode active material is ≤ 5%.

[0088] S5. Online monitoring of calcination. The positive electrode active material obtained in step S4 is placed in a box furnace coupled with an online thermogravimetric analysis system, and inert gas is introduced into the furnace at a flow rate of 4 L / min ± 0.5 L / min.

[0089] Set the calcination program with a target temperature of 475℃ and a target duration of 1.5h, starting the heating process at a rate of 5℃ / min from 25℃±5℃.

[0090] Start the calcination process and simultaneously activate the online thermogravimetric monitoring system to record the cumulative loss on burn rate in real time.

[0091] When the cumulative loss on ignition is 1.7wt%, the actual temperature of the box furnace is 470℃, and the actual calcination time is 1.3h. At this point, the box furnace is stopped from calcining, and the calcination process is terminated.

[0092] Lithium iron phosphate is obtained after cooling in the furnace.

[0093] S6. Fine crushing. The lithium iron phosphate from step S5 is fed into an air jet mill until D50 is 1.2μm±0.3μm.

[0094] S7. Sieving. Pass the finely crushed lithium iron phosphate from step S6 through 200-mesh and 300-mesh sieves in sequence, and collect the material passing through the sieves.

[0095] Example 2

[0096] The preparation method of Example 2 is basically the same as that of Example 1, except that the cumulative burn-off rate in step S5 is 1.75 wt%.

[0097] Example 3

[0098] The preparation method of Example 3 is basically the same as that of Example 1, except that the cumulative burn-off rate in step S5 is 1.8 wt%.

[0099] Example 4

[0100] The preparation method of Example 4 is basically the same as that of Example 1, except that the water content of the positive electrode active material in step S2 is 3000 ppm.

[0101] Example 5

[0102] The preparation method of Example 5 is basically the same as that of Example 1, except that the water content of the positive electrode active material in step S2 is 3800 ppm.

[0103] Comparative Example 1

[0104] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that the cumulative burn-off rate in step S5 is 1.5 wt%.

[0105] Comparative Example 2

[0106] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that the cumulative burn-off rate in step S5 is 2 wt%.

[0107] Comparative Example 3

[0108] The preparation method of Comparative Example 3 is basically the same as that of Example 1, except that the water content of the positive electrode active material in step S2 is 5000ppm.

[0109] Comparative Example 4

[0110] The preparation method of Comparative Example 4 is basically the same as that of Example 1, except that the water content of the positive electrode active material in step S2 is 7000ppm.

[0111] Comparative Example 5

[0112] Lithium iron phosphate is recovered using a short-time dynamic sintering method. Specifically, the waste positive electrode sheet is made into fragments with an average side length of 10mm, which are then fed into an integrated rotary kiln and sintered at 330℃ for 0.5h under a nitrogen atmosphere. After sintering, the material is transferred to a cooling sub-kiln and allowed to cool naturally to below 50℃. The material is then taken out and fed into a crushing device for crushing until the Dv50 is 0.8μm~1.5μm, thereby recovering lithium iron phosphate from the waste positive electrode sheet.

[0113] Comparative Example 6

[0114] Lithium iron phosphate is recovered using a long-term static sintering method. Specifically, the waste positive electrode sheet is made into fragments with an average side length of 10mm, placed in a sagger and fed into a roller kiln, and sintered at 550℃ for 3 hours under a nitrogen atmosphere. After sintering, the material is allowed to cool naturally to below 50℃, and then taken out and fed into a crushing device for crushing until the Dv50 is 0.8μm~1.3μm, thus recovering lithium iron phosphate from the waste positive electrode sheet.

[0115] Comparative Example 7

[0116] Lithium iron phosphate is recovered using a dry pulverization and non-sintering method. Specifically, the waste positive electrode sheet is made into fragments with an average side length of 10mm, fed into a horizontal turbine mill, and then fed into a vibrating screen to separate aluminum foil and positive electrode active material. The fragments are then subjected to an air classifier mill until the Dv50 is 0.8~1.8μm, and lithium iron phosphate is recovered from the waste positive electrode sheet.

[0117] The lithium iron phosphate samples from various embodiments and comparative examples were tested, including...

[0118] (1) The aluminum content of impurities was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) to separate the waste positive electrode active material.

[0119] (2) Magnetic foreign matter (MI) content: magnetic foreign matter in lithium iron phosphate recovered by adsorption with a magnetic rod is dispersed in water or ethanol, and the magnetic foreign matter is digested and diluted with acidic solution. The content of iron, cobalt, chromium, nickel and zinc in the magnetic foreign matter is determined by inductively coupled plasma atomic emission spectrometry and the total content of each element is calculated.

[0120] The lithium iron phosphate samples from the various embodiments and comparative examples were assembled into coin cells according to the following method, and their electrochemical performance was tested:

[0121] Lithium iron phosphate, PVDF binder, and acetylene black conductive agent were mixed in a mass ratio of 97%:1.5%:1.5% to form a positive electrode slurry, which was then coated onto an aluminum foil current collector and dried to form a positive electrode sheet. CR2025 coin cells were assembled using a lithium metal sheet as the negative electrode sheet, a commercial PP film as the separator, and a 1 mol / L LiPF6+EC / DMC electrolyte. Finally, charge-discharge tests, rate performance tests, and cycle performance tests were conducted on a coin cell testing cabinet.

[0122] The charge / discharge test involves conducting a charge / discharge test at a current density of 0.1C, with a test voltage range of 2.0V to 3.75V, to test the first charge capacity, first discharge capacity, and first coulombic efficiency of the coin cell.

[0123] Cyclic performance test: 100 charge-discharge cycles were performed at a current density of 0.1C. The battery discharge capacity retention rate after 100 cycles was calculated as: capacity retention rate = first cycle discharge capacity / 100 cycle discharge capacity × 100%.

[0124] Rate performance test: Constant current charge and discharge test was performed at 5C rate, with a test voltage range of 2.0V~3.75V.

[0125] The performance test results are shown in Table 1. Figure 2 and Figure 3 .

[0126] Table 1

[0127]

[0128] Based on Table 1 above Figure 2 It can be seen that the cumulative burn-off rate of Comparative Example 1 is less than 1.7 wt%. The waste lithium iron phosphate in Comparative Example 1 was underburned, and the key reactions of binder decomposition, amorphous carbon reconstruction and crystal repair were not fully completed, resulting in the loss of electrochemical performance of the regenerated lithium iron phosphate. The cumulative burn-off rate of Comparative Example 2 is more than 1.8 wt%. The waste lithium iron phosphate in Comparative Example 1 was overburned, and the regenerated lithium iron phosphate itself underwent thermal decomposition or excessive amorphous carbon ablation, resulting in a decrease in intrinsic electrochemical activity.

[0129] Comparative Examples 3 to 4 Figure 3 It can be seen that the water content of the waste lithium iron phosphate after vacuum drying exceeds 4000ppm, and its capacity retention rate is significantly lower than that of Examples 1 to 5. The cycle retention rates of Examples 1, 3 and 4 are all greater than 96.5%, while the capacity retention rates of Comparative Examples 3 and 4 are significantly lower. This indicates that controlling the water content of the waste lithium iron phosphate within an optimal range is an important factor in determining the timing of calcination cessation and thus controlling the regeneration process in a closed loop by using the cumulative burn-off rate.

[0130] Comparative Example 5 uses short-time dynamic sintering. After the waste positive electrode sheet is sintered in a rotary kiln, under the rotating sintering condition of 330℃, friction and collision occur inside the material and with the furnace wall, resulting in a large amount of aluminum chips and impurities being mixed into the positive electrode active material. In addition, the sintering time is relatively short, and the degree of decomposition of the binder is not sufficient. Under-sintering results in the first discharge capacity of the recovered lithium iron phosphate being 155.5mAh / g, which does not meet expectations. This shows that short-time dynamic sintering is difficult to balance the control of impurity content and high-quality recovery of lithium iron phosphate.

[0131] Comparative Example 6 employed long-term static sintering. The waste positive electrode sheet was placed in a sagger and fed into a roller kiln. The internal heating of the waste positive electrode sheet in the sagger was uneven, resulting in poor consistency in the quality of the recovered lithium iron phosphate. Furthermore, its first-cycle discharge capacity was 155.5 mAh / g, and its cycle retention rate was 95.1%, which did not meet expectations. This indicates that the static sintering method is prone to uneven processing, with some materials being under-burned and others over-burned, making it difficult to recover high-quality and consistent lithium iron phosphate products.

[0132] Comparative Example 7 uses dry grinding without sintering. The waste positive electrode sheet is subjected to turbine sand milling and vibration separation of positive electrode active material and aluminum foil. Since the binder did not fail during the mechanical separation process, the Al and MI content in the recovered lithium iron phosphate exceeded the tolerance expectation, indicating that the organic binder was not effectively removed, making it difficult to recover high-quality lithium iron phosphate products.

[0133] Combined with Examples 1 to 5 Figure 2 and Figure 3This application demonstrates that when the water content of waste lithium iron phosphate is controlled below a certain level, the optimal window for controlling the cumulative loss on ignition is 1.7wt% to 1.8wt%, resulting in regenerated lithium iron phosphate with superior electrochemical performance.

[0134] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0135] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for recycling waste positive electrode sheets, characterized in that, Includes the following steps: The positive electrode active material layer is peeled off from the positive electrode waste, and the positive electrode active material is subjected to vacuum drying and calcination treatment in sequence to obtain lithium iron phosphate. The water content in the positive electrode active material after vacuum drying is controlled to be ≤4000ppm; the cumulative burn-off rate of the positive electrode active material is monitored during the calcination process, and heating is stopped and cooling is initiated when the cumulative burn-off rate is 1.7wt%~1.8wt%.

2. The method for recycling waste positive electrode sheets as described in claim 1, characterized in that, The calcination treatment satisfies one or more of the following conditions: (1) The calcination process is set to a temperature of 450℃~500℃; (2) The calcination process is set to last for 1 to 2 hours; (3) The heating rate of the calcination treatment is 3℃ / min to 7℃ / min; (4) The calcination process is carried out in an inert gas with a flow rate of 0.5 L / min to 5 L / min.

3. The method for recycling waste positive electrode sheets as described in claim 1, characterized in that, The vacuum drying process satisfies one or more of the following conditions: (1) The vacuum degree of the vacuum drying process is -0.05MPa to -0.1MPa; (2) The drying temperature of the vacuum drying process is 100℃~150℃; (3) The drying time of the vacuum drying process is 30 min to 150 min.

4. The method for recycling positive electrode waste as described in any one of claims 1 to 3, characterized in that, After the positive electrode active material undergoes the vacuum drying process and before the calcination process, the following steps are also included: The positive electrode active material, after being vacuum dried, is coarsely crushed to D90 < 100 μm to obtain coarsely crushed positive electrode active material.

5. The method for recycling waste positive electrode sheets as described in claim 4, characterized in that, Different batches of the coarsely crushed positive electrode active material are mixed, and the mixing process satisfies one or more of the following conditions: (1) The rotation speed of the mixing process is 25 rpm to 40 rpm; (2) The mixing time is 15 min to 120 min; (3) The temperature of the mixing process is 25℃~50℃; (4) The atmosphere of the mixed treatment is one or more of air atmosphere and nitrogen atmosphere.

6. The method for recycling positive electrode waste as described in any one of claims 1 to 3, characterized in that, After the calcination treatment and before obtaining the lithium iron phosphate, the following steps are also included: The lithium iron phosphate obtained from the calcination treatment is subjected to fine crushing treatment to control the D50 of the obtained lithium iron phosphate to be 1μm~5μm.

7. The method for recycling positive electrode waste as described in any one of claims 1 to 3, characterized in that, The positive electrode active material layer is peeled off from the positive electrode waste, including the following steps: The positive electrode waste is soaked in water and separated to obtain the positive electrode active material.

8. A lithium iron phosphate, characterized in that, It is recovered using the recycling method for positive electrode waste as described in any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that, Including lithium iron phosphate as described in claim 8.

10. A lithium-ion battery, characterized in that, It includes the positive electrode, the negative electrode, and the separator and / or electrolyte disposed between the positive electrode and the negative electrode as described in claim 9.